Racial Reconciliation and Inclusive Excellence at Church-Related Colleges and Universities. Issue 1 (15th March 2018) - Allen, Todd; Custer, Dan
ABSTRACT: In recent years, the topic of multiculturalism has often been a divisive issue. Although some argue that highlighting particularities allows for richer and more productive dialogue across differences, others choose to emphasize humankind's similarities with the belief that this focus on commonalities will create a greater sense of unity. This article addresses how Christian colleges and universities can enter this conversation using the ideology of reconciliation and the framework of inclusive excellence to offer a way forward. The authors conclude with remarks on the characteristics of inclusively excellent institutions as well as recommendations for action.